Analysis Nozzle Temperature Effect in 3D Printer Fused Deposition Modelling (FDM) On Mechanical Properties and Characteristics of Polylactic Acid (PLA) - Setiawan, Agris; Rizky, Muhamad Alfa; Sukamto, Untung (Universitas Sebelas Maret, 2022)
Fused Deposition Modelling (FDM) 3D Printer is a revolutionary technology inAdditive Manufacturing (AM). Polylactic Acid (PLA) is a biodegradable andcompostable polymer formed from the condensation of lactic acid. This experimentalstudy uses a nozzle temperature variation of 210 °C, 220 °C, 230 °C and infill type ishoneycomb pattern which print speed of 3D printer is 80mm/s to print the specimen.The specimen of tensile test was conducted based on American Society for Testing andMaterial (ASTM) standard D638 type 4, while the specimen of flexural test wasconducted based on ASTM standard D790. tensile test, flexural test, andmacrostructural analysis will be carried out to determine the effect of nozzletemperature on the test. Based on the results of the study, it was found that the shrinkageproduced by 3D Print specimens for tensile tests and flexural tests at nozzletemperature 230 °C was very high, namely 2.83% and 4.33%, respectively. nozzletemperature at 230 °C produces a fairly high Ultimate Tensile Strength (σUTS) andFlexural strength (σFS) of 39.60±2.60 MPa and 49.02±0.76 MPa, respectively. Inmacrostructural analysis, the nozzle temperature porosity at 230 °C produces thesmallest porosity of 0.04 mm2 or 1.46%.